A Review: Mechanical Properties of Recycled Aggregate Concrete and its Optimum Content in Concrete - WONG, WOEI CHEN; MOHAMAD, NORIDAH (Recent Trends in Civil Engineering and Built Environment, 2022)
Recycled aggregate concrete as structural materials can avoid the depletion in natural resources because major natural resources such as cement and virgin aggregates are needed in huge amount in manufacturing concrete in building construction. The aim of this study is to investigate the optimum content of recycled aggregates that used in concrete. Compressive strength, splitting tensile strength and modulus of elasticity of recycled aggregate concrete were analysed from previous studies. It was found that as percentage of recycled aggregates increases, the mechanical strength of concrete will decrease. However, a substitution of about 25% to 50% of recycled aggregates have insignificant influence on its mechanical properties of recycled aggregate concrete.